Does nature-based social prescription improve mental health outcomes? A systematic review and meta-analysis - Menhas, Rashid; Yang, Lili; Saqib, Zulkaif Ahmed; Younas, Muhammad; Saeed, Muhammad Muddasar (Frontiers in Public Health, 2024)
Background: A nature-based social prescription (NBSP) is an approach to improving mental health outcomes that involves prescribing nature-based interventions as complementary or alternative therapy to traditional ones. A variety of advantages are available from NBSP for people looking to enhance their mental well-being. The effect size of NBSPs has not been thoroughly evaluated by systematic reviews and meta-analyses. Objectives: The current study aimed to analyze existing studies and conduct a meta-analysis to determine the overall effect size of NBSP's outcomes on mental health. Methods: By choosing the relevant papers from among those that were available, a meta-analysis was carried out in the current study. A systematic search of electronic databases (Pub Med, Web of Science, Scopus, Cochrane Library, Embase, CINAHL, and PsychINFO) was conducted to identify relevant studies. Studies were included if they evaluated the effects of NBSP on mental health outcomes. Effect sizes were calculated using the random effects model. Results: Meta-analysis of interventions statistics shows that CBT (SMD-0.0035; 95% CI: [-0.5090; 0.5020]; Tau^2: 0.1011; Tau: 0.318), digital intervention ( SMD- 0.3654; 95% CI: [-0.5258; 1.2566]; Tau^2: 0.2976, Tau: 0.5455), music intervention (SMD-2.1281; 95% CI: [-0.4659; 4.7221]; Tau^2: 3.4046; Tau:1.8452) and psychological interventions (SMD-0.8529; 95% CI: [0.3051; 1.4007]; Tau^2: 0.1224; Tau: 0.3499) do not significantly impact. The other interventions (social belongingness, communication training, blue intervention, nature-based education, CBGT, social prescribing coordinator, self-help intervention, participatory, organizational intervention, inpatient services, brief diet, internet-based intervention, prenatal intervention, yoga and meditation, ergonomics training program, yoga nidra intervention, and storytelling) highlighted above are significant.